Emergent synthetic approach for management of complexity in production systems. Issue 1 (1st January 2019) - D'Addona, D.M.
Abstract: Industry 4.0 gives guidelines to drive production to overcome the consequences of the 2008 crisis in the manufacturing sector by emphasizing technological innovations, such as industrial internet, cloud manufacturing, etc. The proposed paper focuses on cognitive manufacturing within the framework of the Emergent Synthesis approach. Specifically, a Class III synthesis problem with reference to tool inventory management in a complex manufacturing environment is addressed. Such complex environment is proved to be affected by significant non-random uncertainty involving tool delivery time fluctuations and unpredictable tool demand. To deal with the complexity of the manufacturing environment, this paper presents bounded rationality as a characteristic of agents. The purpose of the implemented multi-agent manufacturing model is to manage the uncertainty in the perception, action and inner structure of the manufacturing system by introducing bounded rationality in agent characteristics and the probability–possibility transformation of historical data. The applicability and efficiency of the developed multi-agent manufacturing model are investigated in a real industrial case study. The results indicate that the complexity of a manufacturing system can be studied and solved as Class III synthesis problem and it is helpful to integrate bounded-rational agents in a multi-agent system.